Fructose: Toxic effect on cardiorenal risk factors and redox state - Francisqueti, Fabiane V. [UNESP]; Santos, Klinsmann C. [UNESP]; Ferron, Artur J. T. [UNESP]; Lo, Angelo T. C. [UNESP]; Minatel, Igor O. [UNESP]; Campos, Dijon H. S. [UNESP]; Ferreira, Ana Lucia A. [UNESP]; Corrêa, Camila Renata [UNESP] (Sage Publications Inc, 2016)
Aim: To investigate the effects of fructose consumption on the antioxidant capacity in heart and kidney, cardiovascular disease risk factors, and evaluation of these variables after its removal. Methods: Male Wistar rats (n = 36) were divided into control group (n = 12): standard chow + water or F group: standard chow + fructose in drinking water (30%) for 15 weeks. After, F group was divided to continue receiving standard chow + fructose in drinking water (30%) (n = 12) or standard chow + water (Ex group, n = 12) for 9 weeks. Water, chow and caloric diaries intake, final body weight, adiposity index, plasma glucose and triacylglycerol, systolic blood pressure, and cardiac and renal hydrophilic antioxidant capacity were analyzed. Results: Control and Ex groups consumed less chow and water compared to F group. Caloric intake was higher in control group. There was no difference in final body weight and adiposity index. Systolic blood pressure and cardiac and renal hydrophilic antioxidant capacity were worst in F group. Conclusion: Prolonged exposure to fructose induces oxidative stress, systolic blood pressure, and increase in triacylglycerol. When stopped fructose consumption, Ex group presented improvement in these variables, suggesting the toxicity effect of fructose when consumed in high amounts and prolonged exposure.
Keywords: Antioxidant imbalance; obesity; blood pressure